Challenges and Opportunities in ESG Investments - Vodenska, Irena; Trajanov, Risto; Chitkushev, Lou; Trajanov, Dimitar (Springer Nature Switzerland, 2022)
Environmental, Social, and Governance (ESG) criteria gain increasing attention by governments and corporations to assess how advanced countries and companies are with sustainability. The adoption of the ESG in-vestment approach addresses risk management issues and sets goals to-ward more responsible behavior. Sustainable development goals adopted by the United Nations in 2015 include a call for action to end poverty, save the planet, and ensure peace and prosperity for all by 2030. This paper studies advanced machine learning methodologies to assess, analyze, and suggest improvements in corporate behavior to comply with global sustainable development goals.
Keywords: ESG (Environmental, Social, and Governance) Investments, Machine learning, AI-based systems, Sustainable Development, Financial and Economic Stability